2011
DOI: 10.5507/ag.2011.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of competition in physical activity and sport on the self-perception of individuals with physical disabilities

Abstract: BACKGROUND: Physical activity has traditionally been treated as one of many strategies to improve an individual's quality of life. Until fairly recently, this presumption has been accepted as truth and little research has been done on proving or disproving the claim. Now, there has been a larger focus on it and numerous studies have analyzed the contribution physical activity has on the individual's quality of life in all areas. OBJECTIVE: This study analyzes the current literature in the area of physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…This means that that they felt physically prepared for the competitions. This finding has been supported by Cocquyt and Sigmund (2011) who found a positive relationship between sport participation and increased self-perception among people with physical disabilities. Additionally, Scarpa (2011) found that adolescents and young adults with physical disabilities who regularly exercise achieved higher scores in global self-esteem and physical self-worth than their peers who did not exercise regularly.…”
Section: Discussionmentioning
confidence: 56%
“…This means that that they felt physically prepared for the competitions. This finding has been supported by Cocquyt and Sigmund (2011) who found a positive relationship between sport participation and increased self-perception among people with physical disabilities. Additionally, Scarpa (2011) found that adolescents and young adults with physical disabilities who regularly exercise achieved higher scores in global self-esteem and physical self-worth than their peers who did not exercise regularly.…”
Section: Discussionmentioning
confidence: 56%
“…This means that that they felt physically prepared for the competitions. This finding has been supported by Cocquyt and Sigmund (2011) who found a positive relationship between sport participation and increased self-perception among people with physical disabilities. Scarpa (2011) found that adolescence and young adults with physical disabilities who regularly exercise achieved higher scores in global self-esteem and physical self-esteem than their peers who did not exercise regularly.…”
Section: Discussionmentioning
confidence: 56%
“…Estas consideraciones anteriores son de mayor calado cuando se trata de alumnado con DM (Hernández, Labrador, Niort, Berbel & Trullols, 2017;Rello, Garoz & Tejero, 2018), ya que estos estudiantes manifiestan dificultades en la elaboración de la imagen corporal y del autoconcepto ante el aprendizaje (Fernández, 2014). Autores como Cocquyt & Sigmund (2011) y Ocete (2015 plantean que la participación en programas de actividad física contribuye a la mejora de la calidad de vida del alumnado con DM. Para facilitar la participación activa sustentada en una intervención docente inclusiva en EF es preciso reducir las barreras para el aprendizaje con una intervención docente de calidad, comprometida con todo el alumnado sin excepciones (Arnáiz, 2003;Echeita, 2006;Izquierdo-Gómez & Díaz-Cueto, 2017;Ríos, 2009) y dando respuesta a la diversidad con una mayor equidad y calidad (Beasley & Garn, 2013;Canales, Aravena, Carcamo-Oyarzun, Lorca y Martínez-Salazar, 2018).…”
Section: Introductionunclassified